2017
DOI: 10.21037/jtd.2017.08.61
|View full text |Cite
|
Sign up to set email alerts
|

Unique distribution of programmed death ligand 1 (PD-L1) expression in East Asian non-small cell lung cancer

Abstract: Background: To determine the proportion and clinical features of programmed death ligand 1 (PD-L1) expression in East Asian non-small cell lung cancer (NSCLC).Methods: PD-L1 expression was assessed by immunohistochemistry (IHC) and tumor proportion score (TPS) with the use of PD-L1 IHC 22C3 antibody (Dako North America) in 108 surgically resected lung squamous cell carcinomas (SCC) and 221 lung adenocarcinomas (LUADs), and was correlated with clinical variables, histologic subtypes, and common driver mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
36
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 22 publications
(21 reference statements)
7
36
2
1
Order By: Relevance
“…In our study, solid and squamous areas were associated with higher PD‐L1 levels, both when comparing between tumours, and when comparing between histotype areas within tumours. The intertumoral aspect of this finding is consistent with prior studies showing that squamous cell carcinomas tended to have higher PD‐L1 levels than adenocarcinomas, and that predominantly solid adenocarcinomas tended to have higher PD‐L1 levels than other adenocarcinomas . Only a minority of the prior studies reported data at both of the clinically relevant thresholds (1% and 50%), and only a subset reported on each of the common adenocarcinoma subtypes .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In our study, solid and squamous areas were associated with higher PD‐L1 levels, both when comparing between tumours, and when comparing between histotype areas within tumours. The intertumoral aspect of this finding is consistent with prior studies showing that squamous cell carcinomas tended to have higher PD‐L1 levels than adenocarcinomas, and that predominantly solid adenocarcinomas tended to have higher PD‐L1 levels than other adenocarcinomas . Only a minority of the prior studies reported data at both of the clinically relevant thresholds (1% and 50%), and only a subset reported on each of the common adenocarcinoma subtypes .…”
Section: Discussionsupporting
confidence: 87%
“…Insights into the adequacy of a tumour block or biopsy sample for PD‐L1 testing may be gained through evaluation of histological features associated with PD‐L1 levels. Although there is no consensus in the literature, some studies have associated differences in PD‐L1 levels between tumours with differences in the architectural growth pattern, or histotype, of the tumours . As NSCLCs often have multiple different histotype areas, different PD‐L1 levels within a tumour may be associated with local variation in histotype.…”
Section: Introductionmentioning
confidence: 99%
“…However, no consensus has been reached. In our study, we found that patients with lung AC were more likely to have PD-L1-positive tumors than patients with SCC, which was consistent with the results of a recent metaanalysis [37] but different from a report on East Asian populations [38]. Since most of the samples included in this study were AC, we cannot exclude the influence of the small sample size of SCC on the reliability of the results.…”
Section: Discussionsupporting
confidence: 81%
“…No significant association was found between tumor size and PD-L1 expression among the subjects in the present study. This finding was contrary to that demonstrated by Yunjian P et al who found that there was a significant association between positive PD-L1 expression (including TPS ≥ 50% and TPS < 50%) in the ADC cohort with large tumor size [21]. Adenocarcinoma was the most common histological type of NSCLC in the current study.…”
Section: Discussioncontrasting
confidence: 99%